Banana weevil resistance and corn hardness in Musa germplasm - Ortíz, R.; Vuylsteke, D.R.; Dumpe, B.; Ferris, R.S.B. (1995)
Banana weevil (Cosmopolites sordidus Germar) is a major limiting factor in the cultivation of plantains and bananas (Musa spp. L.) in sub-Saharan Africa. The larvae damage the crop by tunneling in the corm. Chemical control is feasible but not sustainable, whereas host plant resistance is safe and has long term benefits. Banana weevil damage and infestation levels and corm hardness were assessed in Musa germplasm in order to determine the genetic control and potential mechanisms of resistance to this insect pest. Susceptibility/resistance to weevil was measured by the percentage coefficient of infestation (PCI) and damage in cross sections (CS) of the corm. All plantains were equally susceptible to the banana weevil, while a wild banana accession and some cooking and dessert banana cultivars showed high levels of resistance. Differential genotypic responses were observed in euploid plantain-banana hybrids. Segregation results suggest that host plant response to weevil in Musa is controlled by gene(s) exhibiting partial dominance towards the resistant parent and modifier genes with additive and dosage effects for susceptibility in the plantain parent. In natural banana germplasm, resistant clones showed increased corm hardness, as measured by a penetrometer in longitudinal and cross sections of outer and central corm tissues. This might suggest a non-preference mechanism for weevil resistance. However, the lack of correlation between corm hardness with PCI and CS scores in the segregating progenies suggested that other mechanisms may be more important in conferring resistance to banana weevil.